Collaborating internationally on physician leadership development: why now?. Issue 3 (4th July 2016) - Chan, Ming-Ka; de Camps Meschino, Diane; Dath, Deepak; Busari, Jamiu; Bohnen, Jordan David; Samson, Lindy Michelle; Matlow, Anne; Sánchez-Mendiola, Melchor
Abstract : Purpose: This paper aims to highlight the importance of leadership development for all physicians within a competency-based medical education (CBME) framework. It describes the importance of timely international collaboration as a key strategy in promoting physician leadership development. Design/methodology/approach: The paper explores published and Grey literature around physician leadership development and proposes that international collaboration will meet the expanding call for development of leadership competencies in postgraduate medical learners. Two grounding frameworks were used: complexity science supports adding physician leadership training to the current momentum of CBME adoption, and relational cultural theory supports the engagement of diverse stakeholders in multiple jurisdictions around the world to ensure inclusivity in leadership education development. Findings: An international collaborative identified key insights regarding the need to frame physician leadership education within a competency-based model. Practical implications: International collaboration can be a vehicle for developing a globally relevant, generalizable physician leadership curriculum. This model can be expanded to encourage innovation, scholarship and program evaluation. Originality/value: A competency-based leadership development curriculum is being designed by an international collaborative. The curriculum is based on established leadership and education frameworks. The international collaboration model provides opportunities for ongoing sharing, networking and diversification.